2022
DOI: 10.3390/jpm12010103
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of the Prognosis of Septic Shock Patients from Before to After the Onset of the COVID-19 Pandemic: A Retrospective Single-Center Clinical Analysis

Abstract: In this study, we investigated the mortality of septic shock patients visiting emergency departments (ED) before and after the coronavirus disease (COVID-19) pandemic onset. We retrospectively reviewed medical records and National Emergency Department Information System data of septic shock patients who visited the ED of a tertiary medical center in South Korea from February 2019 to February 2021. Following the COVID-19 pandemic onset, revised institutional ED processes included a stringent isolation protocol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 19 publications
0
13
0
1
Order By: Relevance
“…In December 2019, coronavirus disease 2019 (COVID-19) emerged in Wuhan, China and soon became a pandemic. During the early stages of the pandemic, the majority of medical resources were focused on the care of patients with COVID-19, and the pandemic impacted the systems of emergency medical centers and affected the diagnosis and treatment processes of patients without COVID-19 [ 1 , 2 , 3 ]. Furthermore, a gap in emergency medical services developed for other diseases, including myocardial infarction, stroke, out-of-hospital cardiac arrest (OHCA), and sepsis, owing to the collateral effects [ 2 , 3 , 4 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In December 2019, coronavirus disease 2019 (COVID-19) emerged in Wuhan, China and soon became a pandemic. During the early stages of the pandemic, the majority of medical resources were focused on the care of patients with COVID-19, and the pandemic impacted the systems of emergency medical centers and affected the diagnosis and treatment processes of patients without COVID-19 [ 1 , 2 , 3 ]. Furthermore, a gap in emergency medical services developed for other diseases, including myocardial infarction, stroke, out-of-hospital cardiac arrest (OHCA), and sepsis, owing to the collateral effects [ 2 , 3 , 4 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…During the early stages of the pandemic, the majority of medical resources were focused on the care of patients with COVID-19, and the pandemic impacted the systems of emergency medical centers and affected the diagnosis and treatment processes of patients without COVID-19 [ 1 , 2 , 3 ]. Furthermore, a gap in emergency medical services developed for other diseases, including myocardial infarction, stroke, out-of-hospital cardiac arrest (OHCA), and sepsis, owing to the collateral effects [ 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. Previous studies have revealed that patients with these life-threatening diseases experienced delays in arrival through overburdened emergency medical services and medical institutions with limited capacity, restricting their access to proper care [ 2 , 3 , 4 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The clinical process in the emergency department also changed. For example, patients with suspected COVID-19 infection had to use isolation rooms, and physicians had to wear personal protective equipment to prevent the spread of COVID-19 infection in South Korea [7] , [8] . These changes might also have impacted the ED revisit.…”
Section: Introductionmentioning
confidence: 99%